(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India has always been referred to as the "Sone ki Chidiya," or the Golden Sparrow, due to its rich cultural legacy. The earliest known examples of Indian art date from circa 3500 BC, and both cultural and religious factors have had a significant impact on their development. The artistic treasures, whether they are paintings, sculptures, poems, or musical compositions, are profoundly influenced by the nation’s unique cultural heritage. India is well known for being a stunning blend of spirituality and modernity, thanks to its magnificent history and breathtaking terrain! Indian art has its roots deep in the history of civilization. It is generally accepted that the majority of Indian art forms emerged during the height of the Indus Valley Civilization. India’s rich artistic heritage, which spans from prehistoric petroglyphs to a thriving modern art scene, is the outcome of several cultural influences. The richness of art from this region is expressed in vibrant, unique, and captivating styles that embody numerous different civilizations. This encompasses everything produced in the historical regions of what is now Bangladesh, India, and parts of Pakistan and Afghanistan. We will take you on an enjoyable journey through the history of Indian art through this paper, exploring its significant moments in addition to a great variety of styles and forms.